BPC 157 as a Therapy for Retinal Ischemia Induced by Retrobulbar Application of L-NAME in Rats - Zlatar, Mirna; Kokot, Antonio; Vuletic, Lovorka Batelja; Masnec, Sanja; Kralj, Tamara; Perisa, Marija Milkovic; Barisic, Ivan; Radic, Bozo; Milanovic, Kristina; Drmic, Domagoj; Seiwerth, Sven; Sikiric, Predrag (Frontiers in Pharmacology, 2021)
Providing NO-system importance, we suggest that one single application of the NOS-blocker L-NAME may induce retinal ischemia in rats, and that the stable pentadecapeptide BPC 157 may be the therapy, since it may interact with the NO-system and may counteract various adverse effects of L-NAME application. A rat retinal ischemia study was conducted throughout 4 weeks, including fundoscopy, behavior presentation, tonometry, and histology assessment. Retrobulbar L-NAME application (5 mg/kg; 0.5 mg/0.1 ml saline/each eye) in rats immediately produced moderate generalized irregularity in the diameter of blood vessels with moderate atrophy of the optic disc and faint presentation of the choroidal blood vessels, and these lesions rapidly progressed to the severe stage. The specific L-NAME–induced vascular failure points to normal intraocular pressure (except to very transitory increase upon drug retrobulbar administration). When BPC 157 (10 μg; 10 ng/kg, as retrobulbar application, 1 μg; 1 ng/0.1 ml saline/each eye) is given at either 20 min after L-NAME or, lately, at 48 h after L-NAME, the regular retrobulbar L-NAME injection findings disappear. Instead, fundoscopy demonstrated only discrete generalized vessel caliber irregularity with mild atrophy of the optic disc, and then, quite rapidly, normal eye background and choroidal blood vessels, which remain in all of the subsequent periods. Also, histology assessment at 1, 2, and 4 weeks shows that BPC 157 counteracted the damaged inner plexiform layer and inner nuclear layer, and revealed normal retinal thickness. The poor behavioral presentation was also rescued. Thus, while further studies will be done, BPC 157 counteracted L-NAME–induced rat retinal ischemia.